Penggunaan Chat Gpt Sebagai Alat Bantu Dalam Proses Pembelajaran Dan Implikasinya Terhadap Motivasi Belajar Mahasiswa - arya, Arya Raj Prambudi; Frans Mikael Sinaga (PT. Intelek Cendikiawan Nusantara, 2024)
This research aims to analyze the use of GPT Chat as a tool in the learning process and its implications for student learning motivation. In an increasingly advanced digital era, artificial intelligence technology, especially Chat GPT, offers great potential in improving the quality of education, including in the context of learning in higher education. This research uses a literature study method to collect and analyze various literature related to the use of GPT Chat in education and its impact on student learning motivation. The study results show that Chat GPT can function as an effective tool in enriching learning material, providing instant feedback, and supporting independent learning. The implications of this research show that the integration of GPT Chat in the learning process has the potential to increase student involvement in academic activities and encourage more active and technology-based learning.